Photo-voicing experiences of teenage mothers with teenage pregnancy and motherhood in Western Uganda - Linda Grace Alanyo; Enos Mirembe Masereka; Pebalo Francis Pebolo; Emmanuel Kimera (PLoS ONE, 2025)
Teenage Pregnancy and Motherhood (TPM) pose significant global public health challenges, particularly in Sub-Saharan Africa with Uganda being among the countries most affected. In this phenomenological study we aimed to understand the lived experiences of teenage mothers regarding TPM, and to develop advocacy materials and methods to combat TPM. We recruited 14 teenage mothers, aged 16–19 years, who were receiving care at a high-volume hospital in Fort Portal City, Western Uganda. Photovoice, a participatory action research method was used, involving five group sessions. Participants documented their TPM experiences through photographs and narratives, followed by group discussions. Data were analyzed using phenomenological hermeneutics, with themes emerging from participants’ lived experiences. Teenage pregnancy and motherhood were understood to be unexpected and undesirable by the girls who experienced them. These situations were often marked by attempts to conceal the pregnancy, such as fleeing from home, and were compounded by insufficient material and psychosocial support. The girls also faced conflicting emotions about having children, challenges related to childbirth and childcaring as well as strained relationships with their families or partners. The unexpected, undesired, and challenging nature of TPM for this population highlights the need for comprehensive societal and systemic interventions to prevent TPM and to provide material and psychosocial support to those that find themselves in this situation. This can be through sexuality education to teenage girls and economic support for teenage mothers. Incorporating teenage mothers’ lived experiences into advocacy efforts offers a novel approach to addressing the TPM challenge in the setting of western Uganda. Teenage pregnancy is a deeply stigmatized and challenging experience for young girls, often leading to social isolation, concealment, and insufficient support, highlighting the urgent need for comprehensive societal and systemic interventions.